2024
DOI: 10.3390/app14083413
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Aerobic Capacity, Anthropometric Characteristics, and Performance in the Yo-Yo Intermittent Recovery Test among Elite Young Football Players: Differences between Playing Positions

Yiannis Michailidis

Abstract: The objectives of this study were to investigate (a) the relationship between the Yo-Yo intermittent recovery test level 1 (YYIR1) and a laboratory test for measuring maximal oxygen uptake (VO2max), (b) the relationships between anthropometric characteristics and variables of the two aerobic tests (field and laboratory), and (c) differences in performance and anthropometric characteristics among five different playing positions. The study involved 27 U17 young soccer players (16.0 ± 0.6 years). They randomly u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…In previous studies, it had been reported that in high level football the VO2max could be >60 mL/kg/min [63], but in recent studies the values were 58 ± 5.2 mL/kg/min and 13.4 ± 1.3 km/h for VO2max and vRER, respectively [27], and between 17.7 ± 1 km/h and 18.0 ± 0.9 km/h for vVO2max [64]. For playing position, the study by Modric et al [51] Similarly to our study results, there were no differences in the VO2max between the players of different playing positions [46,47,51,64,65]. For vRER, our study did not show any difference.…”
Section: Discussionsupporting
confidence: 83%
“…In previous studies, it had been reported that in high level football the VO2max could be >60 mL/kg/min [63], but in recent studies the values were 58 ± 5.2 mL/kg/min and 13.4 ± 1.3 km/h for VO2max and vRER, respectively [27], and between 17.7 ± 1 km/h and 18.0 ± 0.9 km/h for vVO2max [64]. For playing position, the study by Modric et al [51] Similarly to our study results, there were no differences in the VO2max between the players of different playing positions [46,47,51,64,65]. For vRER, our study did not show any difference.…”
Section: Discussionsupporting
confidence: 83%